Pasture grasses for hot arid region and their production technology - Rajora, M. P.; Bhatt, R. K.; Patidar, M. (Indian Farming, 2018)
The economy of the farmers of the Thar desert is mainly dependent on mixed-farming. The fodder is mostly shortage in supply as the prevailing biotic and abiotic factors exert pressure on biomass production. In this situation perennial grasses, viz. buffel grass, bird wood grass, sewan, gramna, murath and marvel grass which produce high forage yields can support the animal-based farming system in arid zone. Range grasses of arid zone and their cultivation practices, viz. selection of site, field preparation, protection, choice of species, improved varieties, fertilizer application, sowing time, sowing method, seeding rate, weeding utilization of pasture, yield potential, seed production and maintenance of pasture discussed in this article will aid in pasture establishment in arid zone.